MANAJEMEN KONFLIK PADA PERUSAHAAN KELUARGA (STUDI KASUS PADA PERKEBUNAN X) - Yolla Margaretha (Universitas Kristen Maranatha, 2019)
The economy of a country is supported by the role and contribution of entrepreneurs. They are the driving force for economic growth and one of them is contribution by family business. Even in some developed countries, family companies are the main source of their economy. However, internal management often creates conflicts, which can have a positive and negative impact. This will certainly affect the growth of the family company business. Therefore, good conflict management is needed to resolve conflicts. The role of family business stakeholders must be able to act and play a professional role. In this company, the root of the conflict is the inconsistency of communication between stakeholders in the company, thus triggering mismanagement and hampering the development of the company. Keywords: Conflict; Family Business